Sistema web para la gestión de riesgos laborales. - Maza Lavanda, Flor María (2014)
This document contains everything related to the development of a Web System for Occupational Risk Management based for the needs of Control Area of Occupational Hazards of the Ecuadorian Institute of Social Security, which was considered as the study subject. The OPENCRAEL System is a web application that facilitates the management in the control of occupational risks of any institution or company, as it is designed so that it can be adapted and configured according to the requirements of each of them; its main function is to allow an automated control of information of employees who suffer workplace accidents and entitled to compensation. OPENCRAEL basically allows recording the whole Control of Occupational Hazards proses, facilitating and speeding up the process mentioned. Also allows you to store the information securely. The OPENCRAEL System is a tool that will serve mainly to improve the current situation both in the area of Work Risk in IESS Loja, as in any public or private entity that needs to manage the work risks.